The use of the indefinite article with proper nouns in the French language - E. L. Lukomskaya (Тонкие химические технологии)
The article deals with the use of indefinite article with proper nouns. The role of proper nouns in a sentence is investigated. Three types of interpretation of proper nouns are given.